The Influence of new media on Political Communication (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The voter awareness techniques, new media and media enterprises that influence politicalparties in developing economies through their network partners are explored. As a rule, politicians indeveloping countries play a bigger role than those in the more industrialized western nations. A newmedia campaign was used to affect four major characteristics of the vote bank strategy in the 2014 Indianlegislative elections by analyzing how political management issues were managed and controlled by newmedia collaborators. A political institution must constantly monitor, evaluate, synthesize, and displaypolitical information gathered through social media, Social media platforms to examine as well as anenormous amount of data to filter through